The implementation of Circles of Support and Accountability in the United States. (November 2015) - Elliott, Ian A.; Zajac, Gary
Abstract: According to estimates from the U.S. National Reentry Resource Center (NRRC), at least 95% of state prisoners are released back to their communities after a period of incarceration. The complex issue of returning individuals convicted of sex offenses to their communities often evokes particular concern for both criminal justice agencies and the general public. Amid increases in the scope and intensity of sex offenders' supervision, there has been a growing interest among academics, criminal justice practitioners, and faith groups in using restorative justice approaches with this population. Circles of Support and Accountability (CoSA) is a restorative justice-based community reentry program for sex offenders deemed to be at the highest risk of reoffending and with little or no pro-social community support. This integrative review synthesizes both the previous literature on the effectiveness of CoSA in reducing reoffending with findings from a recent evaluability assessment of CoSA provision in the US. It describes the various forms of implementation, the methods by which CoSA has and can be evaluated, and the possible obstacles that impede rigorous evaluation. The implications for the future implementation and evaluation of CoSA are discussed along with the implications for reentry policy and practice in general. Highlights: Circles of Support and Accountability is a restorative justice-based community reentry program for high-risk, high-need sex offenders. Previous studies of CoSA vary in quality and do not yet establish CoSA as an evidence-based program for reducing sexual recidivism. An evaluability study was carried out at five CoSA sites across the United States to examine program intent and evaluation readiness. Although an experimental evaluation of CoSA was conceivable at those sites visited, obstacles to evaluation exist that need to be addressed. CoSA may need to sacrifice program flexibility in order to demonstrate effectiveness and increase credibility as a criminal justice program.